TangShenWeiNing Formula Prevents Diabetic Nephropathy by Protecting Podocytes Through the SIRT1/HIF-1α Pathway - Chang, Jing; Zheng, Jinsu; Gao, Xia; Dong, Hengbei; Yu, Haitian; Huang, Mengxiu; Sun, Zhencheng; Feng, Xiaomeng (Frontiers in Endocrinology, 2022)
Background: Diabetic nephropathy (DN) represents a major complication of diabetes, and podocyte injury has a critical function in DN development. TangShenWeiNing formula (TSWN) has been demonstrated to efficiently decrease proteinuria and protect podocytes in DN. This work aimed to explore the mechanism by which TSWN alleviates DN and protects podocytes. Methods: The major bioactive components of TSWN were detected by mass spectrometry (MS) and pharmacological databases. Eight-week-old male C57BLKS/J db/m and db/db mice were provided pure water, valsartan, low dose TSWN, middle dose TSWN and high dose TSWN by gavage for 12 weeks, respectively. Results: MS and network pharmacology analyses suggested that TSWN might prevent DN through the sirtuin (SIRT)1/hypoxia-inducible factor (HIF)-1α pathway. Diabetic mice showed elevated urinary albumin-to-creatinine ratio (UACR) in comparison with non-diabetic mice, and TSWN decreased UACR in diabetic mice. Histological injury increased in the kidney in diabetic mice, which could be improved by TSWN. Fibrosis and collagen I expression were induced in the diabetic mouse kidney in comparison with the non-diabetic mouse kidney; TSWN alleviated these effects. Apoptosis and cleaved caspase-3 were induced in the diabetic mouse kidney in comparison with the non-diabetic mouse kidney, and TSWN blunted these effects. Podocytes were damaged in the diabetic mouse kidney, which was improved by TSWN. Podocin and nephrin amounts were decreased in the diabetic mouse kidney in comparison with the non-diabetic mouse kidney, and podocalyxin was increased in urine of diabetic animals in comparison with non-diabetic counterparts. After TSWN treatment, podocin and nephrin were raised in the diabetic mouse kidney, and urinary podocalyxin was depressed in diabetic animals. Diabetic mice had lower SIRT1 and higher HIF-1α amounts in kidney specimens in comparison with non-diabetic mice, and TSWN promoted SIRT1 and inhibited HIF-1α in the diabetic mouse kidney. Moreover, co-staining of SIRT1 and podocin revealed that SIRT1 decreased in podocytes from diabetic mice in comparison with those from non-diabetic mice, and TSWN elevated SIRT1 in podocytes. Conclusions: This study indicated that TSWN alleviates DN by improving podocyte injury through the SIRT1/HIF-1α pathway in diabetic mouse kidneys.